2016
DOI: 10.1128/jvi.00139-16
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Mutagenesis of Guinea Pig Cytomegalovirus Using CRISPR/Cas9-Mediated Gene Editing

Abstract: The cytomegaloviruses (CMVs) are among the most genetically complex mammalian viruses, with viral genomes that often exceed 230 kbp. Manipulation of cytomegalovirus genomes is largely performed using infectious bacterial artificial chromosomes (BACs), which necessitates the maintenance of the viral genome in Escherichia coli and successful reconstitution of virus from permissive cells after transfection of the BAC. Here we describe an alternative strategy for the mutagenesis of guinea pig cytomegalovirus that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 55 publications
(72 reference statements)
0
29
0
Order By: Relevance
“…Several reports have used transfection-infection-based methods to knock out PRV genes, with knockout ratios ranging from 12.5 to 42.9% (14,19). Another large DNA viral genome was reportedly used as part of a strategy to efficiently introduce targeted deletions by this method (37). In that study, CRISPR-mediated gene editing of guinea pig cytomegalovirus was evaluated (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have used transfection-infection-based methods to knock out PRV genes, with knockout ratios ranging from 12.5 to 42.9% (14,19). Another large DNA viral genome was reportedly used as part of a strategy to efficiently introduce targeted deletions by this method (37). In that study, CRISPR-mediated gene editing of guinea pig cytomegalovirus was evaluated (37).…”
Section: Discussionmentioning
confidence: 99%
“…Another large DNA viral genome was reportedly used as part of a strategy to efficiently introduce targeted deletions by this method (37). In that study, CRISPR-mediated gene editing of guinea pig cytomegalovirus was evaluated (37). The authors first transfected CRISPR constructs for 48 h and then added puromycin to kill the untransfected cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the use of CRISPR/Cas9 to target cytomegaloviruses are limited to two recent reports (Bierle, Anderholm, Wang, McVoy, & Schleiss, ; van Diemen et al, ). Bierle et al () showed that by transient transfection of CRISPR/Cas9 constructs carrying anti‐GP133 gRNAs, indel mutations could be introduced at the guinea pig cytomegalovirus target site, thereby inactivating the gene.…”
Section: Crispr/cas9‐targeting Of Human Herpesvirusesmentioning
confidence: 99%
“…Studies on the use of CRISPR/Cas9 to target cytomegaloviruses are limited to two recent reports (Bierle, Anderholm, Wang, McVoy, & Schleiss, ; van Diemen et al, ). Bierle et al () showed that by transient transfection of CRISPR/Cas9 constructs carrying anti‐GP133 gRNAs, indel mutations could be introduced at the guinea pig cytomegalovirus target site, thereby inactivating the gene. Additionally, the authors could direct the deletion of large segments of the viral gene by co‐transfection of two gRNAs, and they succeeded in epitope tagging of GP133 by HDR upon co‐delivery of a gRNA and donor template carrying an Human influenza hemagglutinin (HA)‐tagged version of the gene (Bierle et al, ).…”
Section: Crispr/cas9‐targeting Of Human Herpesvirusesmentioning
confidence: 99%
See 1 more Smart Citation